The impact of human resources architecture on psychological empowerment, a case study at the College of Administration and Economics / University of Kufa - ليث زهير عبد الامير السكافي (Iraqi Journal for Administrative Sciences, 2024)
The current research aims to explore the correlation between Human Resources Architecture and Psychological Empowerment, interpret the nature of the conceptual and philosophical relationship between them and what is the impact of the application techniques of Human Resources Architecture in Psychological Empowerment. This is a way of reducing the knowledge gap between the variables of research. Thus, it is possible to achieve this by testing correlations between Human Resources Architecture and Psychological Empowerment and what is their impact on each other, where the scholar distributed a questionnaire to 180 the number of Faculty members and employees were retrieved 171 valid questionnaires for analysis. The theoretical results showed a knowledge gap in interpreting the nature of the relationship between Human Resources Architecture and Psychological Empowerment in organizations in general and in the organization in question in particular. As a result, it was drafted some recommendations, which will hopefully be taken advantage of by the researchers based on the empirical results that showed a moral and positive correlation between Human Resources Architecture and Psychological Empowerment. Moreover, having a significant effect and positive Human Resources Architecture in Psychological Empowerment. These results came out through validated research hypotheses that were used several research methods, which were represented on average, standard deviation, variance, as well as Cronbach’s alpha coefficient of correlation and regression.